Improving Higher Order Thinking Skills Through Multidimensional Curriculum Design at the High School Level - Nirmalasari; Wahyudin, Dinn; Darmawan, Deni (Jurnal Pendidikan Indonesia, 2024)
This research is motivated by problems in the field which show that the curriculum in schools has not optimally honed students' high-level thinking abilities. This research aims to determine the effectiveness of a multidimensional curriculum in improving high school students' higher order thinking skills. The approach used in this research is a quantitative approach. The method used is quasi-experimental by testing a multidimensional curriculum model integrated with scientific, creative and future thinking competencies in the experimental group and comparing it with the control group. The participants involved were 300 high school students spread across 7 schools. The instrument used to measure students' thinking skills is a questionnaire that contains three dimensions, namely scientific, creative and future thinking. The scientific thinking dimension contains inquiry skills, the creative thinking dimension contains ways of solving problems, and the future thinking dimension contains individual views and time. The results of the study showed that the high-level thinking skills in the experimental group experienced more significant improvement compared to the control group. The dimensions of ability that experienced the most significant increase were future thinking skills and creative thinking skills. A multidimensional curriculum model must be accompanied by innovative and creative learning strategies or methods that encourage higher order thinking skills in students of various ages. The implication of this research is that the multidimensional curriculum model can be used at the secondary school level in order to improve higher order thinking skills.